Conjunctival Squamous Cell Carcinoma due to Long-term Placement of Ocular Prosthesis. Issue 3 (March 2015) - Hayashi, Ayato; Komoto, Masakazu; Matsumura, Takashi; Horiguchi, Masatoshi; Tanaka, Rica; Arakawa, Atsushi; Mizuno, Hiroshi
<x xml:space="preserve">Abstract</x> Summary: Conjunctival squamous cell carcinoma (SCC) arising from an anophthalmic socket is quite rare, with few reports in the English literature. A 59-year-old man who had used an ocular prosthesis for 40 years had not removed the ocular prosthesis at all during the last 5 years. He had developed a mass on his entire right upper eyelid, and biopsy revealed a moderately differentiated SCC. Orbital exenteration including the upper and lower eyelid skin was performed. The defect was reconstructed with a free forearm flap followed by the placement of a facial epithesis. The pathology revealed an intraepithelial carcinoma on the upper palpebral conjunctiva, which seemed to infiltrate exclusively from that site to the upper eyelid and into the orbit. Other risk factors were not detected; therefore, chronic irritation or microtrauma of the upper conjunctiva from the prosthesis due to persistent prosthesis placement could have been the main trigger for the development of SCC. In cases where the ocular prosthesis is not fitted properly or removed appropriately, clinicians should be aware of this possible long-term consequence.